Plasmodium vivax, un parasite qui sort de l’ombre : Plasmodium vivax, a parasite coming out of the shadows - Allgower, A; Taylor, W; Chappuis, F; Eperon, G (Groupe Médecine and Hygiène, 2016)
Since 2001, the incidence and mortality of malaria caused by Plasmodium falciparum have declined. However, this trend has not been seen with Plasmodium vivax which has biological features. Severe vivax malaria is increasingly reported in endemic countries even though P. vivax has been thought of as a benign disease. Diagnosis is challenging : the usual rapid diagnostic tests are less sensitive in detecting P. vivax and there is no test for the detection of the dormant forms (hypnozoites). The treatment of the acute phase is an artemisinin based combination, e.g. artemetherlumefantrine. Primaquine, which is the only currently available treatment against hypnozoites for the prevention of relapses, may trigger acute haemolytic anaemia in individuals with G6PD deficiency. >br/>Depuis 2001, l’incidence et la mortalité de la malaria à Plasmodium falciparum ont diminué. Toutefois, cette tendance n’est pas suivie par Plasmodium vivax, qui présente certaines particularités biologiques. Anciennement considérée comme bénigne, de plus en plus de cas sévères de malaria à P. vivax sont rapportés dans les pays endémiques. Le diagnostic peut être difficile : les tests rapides usuels sont moins sensibles pour détecter P. vivax, et il n’en existe aucun pour la détection des formes dormantes (hypnozoïtes). Le traitement de la crise aiguë est une combinaison thérapeutique à base d’artémisinine, par exemple l’artéméther-luméfantrine. La prévention des rechutes repose sur l’administration de la primaquine, seul traitement actuellement disponible contre les hypnozoïtes et limité par le risque de crise hémolytique en cas de déficit en glucose-6-phosphate-déshydrogénase (G6PD).